Implications of FBXW7 in Neurodevelopment and Neurodegeneration: Molecular Mechanisms and Therapeutic Potential - Yang, Yu; Zhou, Xuan; Liu, Xinpeng; Song, Ruying; Gao, Yiming; Wang, Shuai (Frontiers in Cellular Neuroscience, 2021)
The ubiquitin-proteasome system (UPS) mediated protein degradation is crucial to maintain quantitive and functional homeostasis of diverse proteins. Balanced cellular protein homeostasis controlled by UPS is fundamental to normal neurological functions while impairment of UPS can also lead to some neurodevelopmental and neurodegenerative disorders. Functioning as the substrate recognition component of the SCF-type E3 ubiquitin ligase, FBXW7 is essential to multiple aspects of cellular processes via targeting a wide range of substrates for proteasome-mediated degradation. Accumulated evidence shows that FBXW7 is fundamental to neurological functions and especially implicated in neurodevelopment and the nosogenesis of neurodegeneration. In this review, we describe general features of FBXW7 gene and proteins, and mainly present recent findings that highlight the vital roles and molecular mechanisms of FBXW7 in neurodevelopment such as neurogenesis, myelination and cerebral vasculogenesis and in the pathogenesis of some typical neurodegenerative disorders such as Alzheimer’s disease, Parkinson’s disease and Huntington’s disease. Additionally, we also provide a prospect on focusing FBXW7 as a potential therapeutic target to rescue neurodevelopmental and neurodegenerative impairment.